Termitas asociadas en las plantaciones forestales de Simarouba amara Aubl. “marupa” y de Cedrelinga cateniformis (Ducke) Ducke “Tornillo” del Ciefor Puerto Almendra, Loreto-Perú 2021 - Caritimari Saquiray, Lenin (2024)
The study was done in the experimental field of the Forest Research and Teaching Center of the FCF-UNAP, located on the right bank of the Nanay River, the objective of the study was to identify the termites associated in the forest plantations of S. amara Aubl. “marupa” and C. cateniformis (Ducke) Ducke “tornillo”, from plot 15 (0.71 ha) and 20 (0.66 ha), being a research with a qualitative approach, descriptive type and non-experimental design, The inventory of arboreal individuals was conducted, such as recording the nest types of termites, the samples were collected and transported to the laboratory for taxonomic identification. A total of 957 termite individuals were obtained, which belong to the Termitidae family, with the species identified as Ereymatermes sp., Curvitermes sp., Termes sp., Cornitermes sp1 and Anoplotermes sp., associated with the Cedrelinga cateniformis Ducke plantation and Cornitermes sp2 and Nasutitermes guayanae associated with the Simarouba amara Aubl plantation. The plantations of forest species and their surroundings, allow us to see the association of termites present directly in each individual, 50 S. amara Aubl. trees, only 2 trees have termite nests (1 mound and 1 arboreal) and 92 trees of C. cateniformis (Ducke) Ducke 5 trees have termite nests (3 mounds and 2 arboreal), the reason being their habitat distribution in live stems. In so far as the incidence of termites in both plantations, they are low, this indicates that the damage is little in both plots.